ANALISIS CAMEL DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31112119, ELSY OKTARIA (Jurnal Manajemen Update, 2016)
Banking companies are financial institutions which funcion as financial intermediary. Stock return instability owned by the company making an uncertainty for investors. Therefore, it needs an analysis of company performance to determine a company’s condition so there will be no error in deciding to invest. This analysis was used to assess the health level of banking using CAMEL method, a Bank Indonesia standard in assessing bank health level. The population in this study was banking sectors that go public in Indonesia Stock Exchange during the period 2010-2014 as many as 36 banks. The sampling method used was the purposive sampling method to obtain representative sample appropriate with determined criteria. There were 20 banking companies as sample. There were two variable in this study, independent and dependent variable. Independent variable consist of CAR, NPL, ROA, and LDR. While dependent variable was the value of go public banking companies in Indonesia Stock Exchange. It can be conclude from this study result that CAR, NPL, ROA, and LDR had influence on the value of banking companies listed in Indonesia Stock Exchange in the periode 2010-2014. From the entire ratio, ROA ratio was the ratio of the most dominant influence on the value of the companies. Kata Kunci : CAR, NPL, ROA, LDR dan nilai perusahaan.